The effect of variation of dose, time toward cauli flower (Brassica oleracea var BotrytisL.) On hepatic cytochrome P-450 level rats given theophylline - Sunarsih, Endang Sri; hakim, Lukman; ., Sugiyanto; ., Sumantri (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Cytochrome P-450 as a major component enzyme system in drug metabolism. Activity enzyme of cytochrome P-450 was influenced by internal and external factors. Vegetables of Brassicaceae such as cauli flower were often consumed in the long term, its has inductor activity of oxidation enzyme systems and conjugation reactions. Theophylline as a bronchodilator drugs have the unknown effects on hepatic microsomal enzyme, such as cytochrome P-450 and have not been many studies that tried to prove it. The purpose of this study was to prove the effects of Cauliflower and indol on level cytochrome P-450 enzyme. 90 rats were divided into 3 groups. Group I, were given Theophylline 20 mg/kg BW. In group II 30 rats were treated with indole 1,2; 2,4; 3,6 mg/kg BW, and group III 30 rats were treated with cauliflower extract respectively doses 100, 200, 300 g/kg BW. Each dose was given on 10 rats, each group were divided 2 sub-groups were treated for 5, 10 days. On the last day of treatment were given Theophylline 20 mg/kg BW. Cytochrome P-450 enzyme levels were determined by the method of Omura and Sato(Snell, and Mullock,1987). An induction cauliflower and indole did not increased levels of hepatic cytochrome P-450. The long treatment and the increased of administered dose did not enhanced the levels of hepatic cytochrome P-450 enzyme. cauliflower and indole contained in vegetables when consumed together with theophylline drug, would not affect the metabolism of theophyllineKey words: Cauli flower, cytochrome P-450, theophylline, indole, spectrofotometric.